PRAKTIK AKAD, BAGI HASIL, DAN RISIKO GHARAR DALAM TRADISI MAROSOK: SUATU STUDI KASUS PASAR TERNAK MINANGKABAU - Darniati, Lili; Fahlefi, Rizal; Lutfi, Ahmad (JSE: Jurnal Sharia Economica, 2026)
Marosok is a traditional bargaining practice using hand signals that characterizes livestock markets in Minangkabau. This study aims to analyze contract practices, profit-sharing mechanisms, and the potential risk of gharar within the marosok tradition through a case study approach, integrating interview data with findings from a Systematic Literature Review (SLR). The results reveal that marosok aligns with Islamic principles and local customary values (adat salingka nagari) as long as the process is followed by verbal confirmation and conducted with honesty. The role of the intermediary (joki) is permissible according to both adat and Islamic law through the concept of samsarah, yet it can generate gharar when information is manipulated or hidden margins are involved. The study concludes that marosok represents a form of ‘urf shahih custom validated by Islamic law provided that transparency, trustworthiness, and contractual clarity are upheld. The risk of gharar does not stem from the tradition itself but from individual deviations from ethical norms in adat and sharia.